2018
DOI: 10.7874/jao.2017.00290
|View full text |Cite
|
Sign up to set email alerts
|

Role of Emotional Distress in Prolongation of Dizziness: A Cross-Sectional Study

Abstract: Background and ObjectivesDizziness is a common condition in outpatient clinics. Comorbid conditions such as anxiety and/or depression often complicate a patient’s ability to cope with dizziness. The purpose of the present study was to explore the extent of psychiatric distress using the Hospital Anxiety and Depression Scale (HADS) and to compare the results with the subjective severity of dizziness.Subjects and MethodsThe cross-sectional study included a total of 456 consecutive patients presenting with acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 25 publications
4
16
0
6
Order By: Relevance
“…Still, older subjects reported high scores in the DHI questionnaire, suggesting a considerable emotional load anyway and interference of daily activities. Hence, the emotional factor is a substantial handicap to consider also among older adults ( 23 , 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Still, older subjects reported high scores in the DHI questionnaire, suggesting a considerable emotional load anyway and interference of daily activities. Hence, the emotional factor is a substantial handicap to consider also among older adults ( 23 , 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…En ambos grupos se observó una correlación moderada entre la puntuación total de la escala de ansiedad y la discapacidad del vértigo. Lo anterior sugiere que el aumento de los niveles de angustia emocional en pacientes con sintomatología crónica demuestra que el estado emocional puede contribuir en la prolongación de los síntomas de vértigo desde la fase aguda (Roh, Kim, Kim, & Son, 2018).…”
Section: Los Trastornos De Ansiedad Son El Resultado De La Disfunción Vestibularunclassified
“…In a study of the role of emotional disorders in the extent of dizziness, Roh et al [26] found that chronic dizziness patients had higher anxiety depression levels and emotional distress and stated that emotional distress extends the duration of dizziness.…”
Section: Discussionmentioning
confidence: 99%